Formal Rules to Produce Object Notation for EXPRESS Schema-Driven Data - Semenov, V. A.; Arishin, S. V.; Semenov, G. V. (Programming and computer software, 2022)
Currently, product data management (PDM) systems are widely employed to implement complex multidisciplinary projects in various industrial domains. These systems allow teams of designers, engineers, and managers to remotely communicate via a network, as well as exchange and share product information. To integrate CAD/CAM/CAE applications with PDM systems and ensure their interoperability, a dedicated family of STEP standards (ISO 10303) was developed. STEP defines the object-oriented programming language EXPRESS used to formally specify information schemas, as well as file formats designed to store and transfer product data driven by these schemas. These formats are SPF (clear text encoding) and STEP-XML. Presently, with the development and wide spreading of web technologies, the JSON format becomes increasingly popular as it is well suited for object-oriented data exchange and storage, as well as because its syntax is simple and easy to parse. This paper investigates the applicability of JSON to unambiguous representation, storage, and interpretation of product data. On the assumption that product data can be described by arbitrary information schemas in EXPRESS, we propose formal rules for producing JSON notation. Examples that illustrate the proposed rules are provided. Results of our computational experiments confirm the advantages of JSON over SPF and STEP-XML, as well as encourage its wider use for integration of software applications.